Adaptive super-twisting sliding mode control for maximum power point tracking of PMSG-based wind energy conversion systems. (January 2022) - Zholtayev, Darkhan; Rubagotti, Matteo; Do, Ton Duc
Abstract: This paper proposes a super-twisting adaptive sliding mode control law for maximum power point tracking of wind energy conversion systems based on permanent magnet synchronous generators (PMSGs). The employed sliding mode control algorithm can be considered an effective solution, as it retains the robustness properties of classical sliding mode control methods in the presence of disturbances and parameter uncertainties; at the same time, it provides chattering reduction via gain adaptation and generation of second-order sliding modes. In our work, a nonlinear multi-input multi-output tracking control problem is solved to maximize the captured power. Simulation results are presented using real wind speed data, and discussed for the proposed controller and four other sliding mode control solutions for the same problem, in the presence of variations of stator resistance, stator inductance and magnetic flux linkage. The proposed controller achieves the best trade-off between tracking performance and chattering reduction among the five considered solutions: compared to a standard sliding mode control algorithm, it reduces the amount of chattering from two to five orders of magnitude, and the steady-state error on PMSG rotor velocity of one order of magnitude. Also, it reduces the above-mentioned steady-state error of four orders of magnitude with respect to a previously-proposed linear quadratic regulator based integral sliding mode control law for the same system. Graphical abstract: Image 1 Highlights: Maximum power point tracking of PMSG rotor speed in WECSs. Super-twisting sliding mode control with automatic adaptation of control gains. Robustness to parameter variations and external disturbances. Reduction of chattering compared to (adaptive) first-order sliding mode methods. Simulation results provided with real wind speed profile and parameter variations.